If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k + 9 + -10k = 0 Reorder the terms: 9 + 4k + -10k = 0 Combine like terms: 4k + -10k = -6k 9 + -6k = 0 Solving 9 + -6k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -6k = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -6k = 0 + -9 -6k = 0 + -9 Combine like terms: 0 + -9 = -9 -6k = -9 Divide each side by '-6'. k = 1.5 Simplifying k = 1.5
| 81=11x | | 2q+10+q+2q-42+47=360 | | 9y^2-12y+4=169 | | y=1/3(-6)-7 | | -11y=7x-9 | | x^2-2x+y^2+4y+4=0 | | 3t-26+2t+4t-23+3t-20+3t-6=540 | | fx=3x+12 | | (y-7)=9 | | 3b^2-10=98 | | y^2-13=108 | | .66666666666(x-2)=4 | | a^2+8=72 | | 4k^2+9=265 | | 4k(2)+9=265 | | 4y+12x+2+5x-7+13x+4=180 | | 3(23-2x)+3x=16 | | 1.5x-(.5-x)=0 | | 7x+9=0.5(8x-12) | | 4x-(9x+5)=9x-19 | | 1.75x-(.75-x)=0 | | -2x(x-3)=4x+6 | | .2(40x+20)-19=-.5(14x-10) | | 3x(x+3)-6=5x-5 | | 5x-x+x=24 | | 5x+3=10x-9 | | g(x)=4(-5)-5 | | 8x-10=2(4x-7) | | 9(x+8)=5(x-(4-x)) | | (2y-(3y-4)+5y-6)+10y=(12y-12)+36 | | 4x^2-65x+64=0 | | 6x+20=8x+6y |